The evolution of social standards and guarantees in the context of the rule of law: international experience and prospects for development in Ukraine - I.O. Nalyvaiko (Аналітично-порівняльне правознавство)
The article is dedicated to the study of social standards and social guarantees in Ukraine, their evolution, current state, and prospects for development in the context of European integration processes. Social standards play an important role in ensuring social justice, equal opportunities, and a decent standard of living for citizens. They regulate basic social rights, including access to healthcare, education, pension provision, and social insurance. At the same time, social guarantees serve as mechanisms for the practical implementation of these standards, providing citizens with access to essential social goods and services. The article examines the evolution of social standards in an international context, starting from the mid-20th century when international organizations such as the UN and the ILO began actively implementing social norms that became the foundation for modern social protection standards. Special attention is given to the influence of European social standards, particularly the European Social Charter, on Ukraine’s national legislation, and key aspects of the implementation of these standards in the national social protection system are analyzed. A particularly important topic is the issue of financing social standards and the effectiveness of their implementation in Ukraine. The problems of insufficient funding for social programs, the uneven distribution of social services between regions, corruption, and inefficient management of state resources are highlighted. Based on the analysis of the experience of European Union countries, solutions to these problems are proposed, including the introduction of digital technologies for monitoring and controlling the provision of social assistance, which can improve the targeting of social payments and reduce corruption risks. Pension system reform is another important component of the development of social standards in Ukraine. The article provides a detailed analysis of the prospects for the implementation of a funded pension system, which will reduce the burden on the state budget and ensure a more efficient distribution of pension resources among citizens. The introduction of individual pension accounts and additional pension savings will help ensure the stability of the pension system in the long term. The article also highlights the role of international organizations and their influence on the development of social standards in Ukraine. The activities of organizations such as the European Union, the International Labour Organization, and others are analyzed, which, through their programs, contribute to the development of national social policies and the improvement of the level of social guarantees for the citizens of Ukraine. Special attention is paid to the harmonization of Ukrainian legislation with European social standards. The authors of the article emphasize that the implementation of European norms and standards in the field of social protection will promote Ukraine’s further integration into the European community. This, in turn, will improve the standard of living for citizens, ensure the fair distribution of social benefits, and create a sustainable social protection system that meets the best European practices. The article concludes with recommendations for comprehensive reforms to Ukraine’s social system aimed at improving social standards and guarantees, taking into account international experience and the realities of the Ukrainian economy. The recommendations focus on the further development of the pension system, improvement of targeted social assistance, and modernization of healthcare. The authors stress the importance of coordinated actions between state institutions, non-governmental organizations, and the private sector to ensure a high level of social protection and a decent quality of life for all Ukrainian citizens.